Methane mitigation potential of foliage of fodder trees mixed at two levels with a tropical grass - Valencia Salazar, Sara Stephanie; Jiménez-Ferrer, Guillermo; Molina Botero, Isabel Cristina; Ku-Vera, Juan Carlos; Chirinda, Ngonidzashe; Arango, Jacobo (MDPI, 2021)
Enteric methane (CH4) emitted by ruminant species is known as one of the main greenhouse gases produced by the agricultural sector. The objective of this study was to assess the potential the potential for CH4 mitigation and additionally the chemical composition, in vitro gas production, dry matter degradation (DMD), digestibility and CO2 production of five tropical tree species with novel forage potential including: Spondias mombin, Acacia pennatula, Parmentiera aculeata, Brosimum alicastrum and Bursera simaruba mixed at two levels of inclusion (15 and 30%) with a tropical grass (Pennisetum purpureum). The forage samples were incubated for 48 h, and a randomized complete block design was used. Crude protein content was similar across treatments (135 ± 42 g kg−1 DM), while P. purpureum was characterized by a high content of acid detergent fiber (335.9 g kg−1 DM) and B. simaruba by a high concentration of condensed tannins (20 g kg−1 DM). Likewise, A. pennatula and P. aculeata were characterized by a high content of cyanogenic glycosides and alkaloids respectively. Treatments SM30-PP70 (30% S. mombin + 70% P. purpureum) and BA30-PP70 (30% B. alicastrum + 70% P. purpureum) resulted in superior degradability at 48h than P. purpureum, while in the AP30-PP70 (30% A. pennatula + 70% P. purpureum) was lower than the control treatment (p ≤ 0.05). At 24 and 48 h, treatments that contained P. aculeata and B. alicastrum yield higher CH4 mL g−1 DOM than P. purpureum (p ≤ 0.05). The inclusion of these forage species had no statistical effect on the reduction of CH4 emissions per unit of DM incubated or degraded at 24 and 48 h with respect to P. purpureum although reductions were observed. The use of fodders locally available is an economic and viable strategy for the mitigation of the environmental impact generated from tropical livestock systems.